Pengaruh Penambahan Tepung Ubi Jalar Ungu dengan Campuran Tepung Beras dan Ketan Terhadap Karakteristik Cimpa - Berena Br Karo, Enita; Suter, I Ketut; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 1 (2022): Jurnal ITEPA, 2022)
This study aimed to determine the effect of addition purple sweet potato flour to rice flour and glutinous rice on Cimpa, and to determine the most appropriate treatment so as to produce the best Cimpa. The experimental design used was a completely randomized design (CRD) with a ratio of rice flour to glutinous rice and purple sweet potato flour consisting of 7 levels: 100%: 0%; 90%: 10%; 80%: 20; 70%: 30%; 60%: 40%; 50%: 50%; 40%: 60%. The treatment was repeated 3 times so that it is obtained 21 experimental units. The data obtained was analyzed with the analysis of variance (ANOVA) and if the variables had a significant effect, followed by The Duncan Multiple Range Test (DMRT). The parameters observed are water content, ash content, protein content, fat content, carbohydrate content and accessory properties including color, aroma, texture, taste and overall acceptance. The results showed that the addition of purple sweet potato flour to mixed rice flour had an effect on moisture content, fat content, color, aroma, taste, and overall acceptance. The best treatment was a composite flour with a ratio of rice flour and glutinous rice to purple sweet potato flour 40%: 60%.